2017
DOI: 10.1534/g3.116.036442
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Characterization of B-Genome Introgression Lines ofBrassica napusL.

Abstract: Brassica napus introgression lines (ILs), having B-genome segments from B. carinata, were assessed genetically for extent of introgression and phenotypically for siliqua shatter resistance. Introgression lines had 7–9% higher DNA content, were meiotically stable, and had almost normal pollen fertility/seed set. Segment introgressions were confirmed by fluorescent genomic in situ hybridization (fl-GISH), SSR analyses, and SNP studies. Genotyping with 48 B-genome specific SSRs detected substitutions from B3, B4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…Generally, introducing genetic variation from the B genome of B. carinata to B. napus is very difficult. To date, only a few cases have successfully introgressed the B genome segments into B. napus, and it would be favourable to introduce the B genome segment to introduce resistance-related genes to B. napus (Dhaliwal et al, 2017;Navabi et al, 2010Navabi et al, , 2011Xiao et al, 2010). Based on the results described above, the inference is that homologous exchange events occurred between the B and A/C genomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, introducing genetic variation from the B genome of B. carinata to B. napus is very difficult. To date, only a few cases have successfully introgressed the B genome segments into B. napus, and it would be favourable to introduce the B genome segment to introduce resistance-related genes to B. napus (Dhaliwal et al, 2017;Navabi et al, 2010Navabi et al, , 2011Xiao et al, 2010). Based on the results described above, the inference is that homologous exchange events occurred between the B and A/C genomes.…”
Section: Discussionmentioning
confidence: 99%
“…These favourable variations may come from the founder parents, but they may also be caused by genomic changes, such as the chromosome rearrangement, homologous recombination, homoeologous shuffling, transposon activation and epigenetic modification. Desirable traits, such as the resistance to disease and pod shatter, that are harboured by the founder parents B. carinata and B. rapa, with high or low heritability, were introgressed to rapeseed easily or arduously through interspecific crossing (Dhaliwal et al, 2017;Diederichsen et al, 2009;Leflon et al, 2007;Raman et al, 2017). For example pod shatter resistance, which is a low heritability trait, was introduced to the B. napus along with the introgression of the B-genome segments from B. carinata, and these introgression lines showed higher pod strength than B. napus parents; some lines were almost equal to that of the B. carinata parents (Dhaliwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that there is limited genetic variation for pod shatter resistance in the natural B. napus germplasm ( Bowman, 1984 ; Raman H. et al, 2014 ). Several research groups around the world are currently using B. carinata to expand the narrow genetic base of B. napus germplasm ( Cowling, 2007 ; Dhaliwal et al, 2017 ). In this study, only one QTL, Qpsr.wwai-C5 was identified on the C subgenome of B. carinata (chromosome C05), while other QTL were identified on the B subgenome (B1, B3, and B8).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only one QTL, Qpsr.wwai-C5 was identified on the C subgenome of B. carinata (chromosome C05), while other QTL were identified on the B subgenome (B1, B3, and B8). Previous studies have shown that fertile plants of B. napus carrying B genome introgressions can be generated ( Navabi et al, 2010 ; Dhaliwal et al, 2017 ). It remains to be established whether B and C genome derived lines exhibit pod shatter resistance expression or get silenced in the resynthesized B. napus ( Xu et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation